Brazil : Staff Report for the 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This 2013 Article IV Consultation highlights that Brazil's economy is recovering gradually from the slowdown that began in mid-2011. Consumption remained resilient last year underpinned by low unemployment and broad gains in real wages, although it has slowed somewhat more recently. After a protracted period of weakness, investment has begun to recover in recent quarters while business confidence has firmed. With the economy estimated to be operating close to potential, supply-side constraints have restrained near-term growth and exacerbated inflationary pressures. Financial conditions have tightened but credit growth has remained strong, driven by public banks' lending.